Efficacy of Using Reading Strategies to Enhance Students’ Achievement in Reading Comprehension: A Case Study at a State School in Battambang - Loem, Sophandara; Ly, Sovann; Nhean, Voithana; Soeurn, Chenda; Ry, Chantha (Journal of English Language Teaching, Literature and Culture, 2025)
The present research study examined the effectiveness of skimming and scanning techniques in enhancing students' reading comprehension, particularly in fostering their critical thinking and problem-solving skills in learning reading comprehension. Thus, this research aimed to investigate the efficacy of using skimming and scanning as reading strategies to improve students' achievement in reading comprehension at a public high school in Battambang. The study involved students at the elementary level of Lvea High School in Bavel District, Battambang Province. The total population consisted of 350 students with 47 students chosen as the sample for this research through purposive sampling. The researcher employed an experimental design with one class receiving the treatment. Data were collected through a pre-test, post-test, and questionnaire. The results indicated a statistically significant difference between the pre-test and post-test scores. The mean score of the post-test (77.48) was higher than the mean score of the pre-test (32.03). Additionally, the t-score (8.62) was greater than the t-table value (2.013) at a significance level of p<0.05 for a two-tailed test, with a degree of freedom of 46. Furthermore, the questionnaire results showed that most of the students responded positively to use skimming and scanning techniques in reading comprehension. Based on the findings, it can be concluded that skimming and scanning techniques significantly enhance students' reading comprehension achievement and are appropriate for implementation.